Hadith #4632 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Ash'uth bin Qays; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
Abu Hurairah said that a man came to the Messenger of Allah (ﷺ) and said: I saw (in my dream) a piece of cloud from which ghee and honey were dropping. I saw the people spreading their hands. Some of them took much and some a little. I also saw a rope hanging from Heaven to Earth. I saw, Messenger of Allah, that you caught hold of it and ascended by it. Then another man caught hold of it and ascended it. Then another man caught hold of it and ascended it. Then another man caught hold of it, bu
Grade: Sahih

Hadith #4660 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Ali bin Zayd bin 'Abdullah bin Zuhayr علي بن زيد بن عبد الله بن زهير; Ash'uth bin Qays; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
When the illness of the Messenger of Allah (ﷺ) became serious while I was with him among a group of people, Bilal called him for prayer. He said: Ask someone to lead the people in prayer. So Abdullah ibn Zam’ah went out and found that Umar was present among the people and AbuBakr was not there. I said: Umar, get up and lead the people in prayer. So he came forward and uttered “Allah is Most Great”. When the Messenger of Allah (ﷺ) heard his voice, as Umar had a loud voice, he said: Wher
Grade: Hasan Sahih